2016
DOI: 10.1007/s40071-016-0127-0
|View full text |Cite
|
Sign up to set email alerts
|

Variations in coastal fish species composition captured by traps in Romsdalsfjord, Western Norway

Abstract: Fish traps are widely used in Norwegian fjords, especially those designed for monitoring salmonid populations in the marine environment, although many other marine fish species are also captured. The composition and spatio-temporal variations of fish species captured by fish traps were monitored in five different coastal locations throughout the Romsdalsfjord region, Western Norway, from May to August during the three consecutive years (2011)(2012)(2013). Twenty-three fish species were captured by traps in coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, the authors identified that the overall prevalence of piscivory at the assemblage level was highest in brackish coastal lagoons, and similar between riverine and marine systems (see Table 4 in Winemiller and Leslie 15 ). The present study suggests otherwise, demonstrating clear differences in piscivory at the population level between riverine and marine systems, but only in multi-species systems as marine ecosystems were only composed by this fish community configuration as a consequence of the difficulties of finding local fish communities composed by few species in the study area 26,27 . It should be noted that the feeding patterns of fish in brackish systems are dissimilar to those observed in freshwater systems as consequence of differences in the size, abundance and diversity of both invertebrate and fish prey 9,28 .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…However, the authors identified that the overall prevalence of piscivory at the assemblage level was highest in brackish coastal lagoons, and similar between riverine and marine systems (see Table 4 in Winemiller and Leslie 15 ). The present study suggests otherwise, demonstrating clear differences in piscivory at the population level between riverine and marine systems, but only in multi-species systems as marine ecosystems were only composed by this fish community configuration as a consequence of the difficulties of finding local fish communities composed by few species in the study area 26,27 . It should be noted that the feeding patterns of fish in brackish systems are dissimilar to those observed in freshwater systems as consequence of differences in the size, abundance and diversity of both invertebrate and fish prey 9,28 .…”
Section: Discussionmentioning
confidence: 58%
“…The different studies vary markedly in scope, sample size and fish community configuration. Because of the high species richness scores in the marine ecosystems 26,27 , these ecosystems only included multi-species systems. Except for one-species systems (only shaped by intraspecific competition), trophic relationships can be diverse as fish species may be prey [e.g.…”
Section: Methodsmentioning
confidence: 99%
“…However, variation in trace element profiles between sampling localities and years indicates that both salmon feed and natural prey (Sanchez-Jerez et al 2002). In addition, changes in migration patterns, natural spatial distribution, or residence time around fish farms may influence the accumulation of trace elements (Arechavala-Lopez et al 2016). For instance, Uglem et al (2009) found that tagged Pollock stayed close to the cages at salmon farms for a prolonged period (days to months), which indicates that the high availability of waste feed originating from salmon farms may influence the accumulation of trace elements.…”
Section: Discussionmentioning
confidence: 99%